Comparison of game development framework and model for parkinson disease rehabilitation - Abd Rauf, Muhammad Fairuz; Kahar, Saliyah; Mohamad Amran, Mohd Fahmi; Marjudi, Suziyanti; Adnan, Zuraidy; Wong, Rita (2023)
Parkinson’s disease patients are consulted to frequently exercise and undergo physiotherapy to reduce the progression rate of their disease. However, this can be a problem when the caretakers that bring them to the rehabilitation center are unavailable due to work or other related issues. The cost to go to re-habilitation is also expensive. Therefore, patients tend to exercise at home where there is no one to monitor except for their caretakers. This can lead to problems in evaluating the progress of the patient’s rehabilitation. The solution for this issue is to develop a game-based rehabilitation. This paper aims to in-vestigate the element for a game-based Parkinson’s disease rehabilitation. Then, the elements are used to develop the preliminary framework which later can be used to develop game-based exercise. A total of eight frameworks and models are studied to identify the core elements. The seven elements which are com-monly used are game design, game mechanics, game engine, patient, therapist, results, and database